2022
DOI: 10.3390/molecules27134323
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide-Residue Analysis in Soils by the QuEChERS Method: A Review

Abstract: Pesticides are among the most important contaminants worldwide due to their wide use, persistence, and toxicity. Their presence in soils is not only important from an environmental point of view, but also for food safety issues, since such residues can migrate from soils to food. However, soils are extremely complex matrices, which present a challenge to any analytical chemist, since the extraction of a wide range of compounds with diverse physicochemical properties, such as pesticides, at trace levels is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 82 publications
(220 reference statements)
0
12
0
Order By: Relevance
“…The Association of Official Agricultural Chemists (AOAC) method was proposed by the International AOAC in 2007 (AOAC 2007.01), and the EN method was proposed by the European Committee for Standardization (EN) in 2008 (EN 15662). 24,48 The purification salts used in each method are as follows: the original method uses magnesium sulfate and sodium chloride; the AOAC method uses magnesium sulfate and sodium acetate; and the EN method uses magnesium sulfate, sodium chloride, sodium citrate dihydrate, and citric acid monohydrate. In this study, we selected 2 g of anhydrous sodium sulfate, 1.0 g of C18, and 0.5 g of copper powder as purification agents and tested the recovery rates under two conditions: with and without the purification step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Association of Official Agricultural Chemists (AOAC) method was proposed by the International AOAC in 2007 (AOAC 2007.01), and the EN method was proposed by the European Committee for Standardization (EN) in 2008 (EN 15662). 24,48 The purification salts used in each method are as follows: the original method uses magnesium sulfate and sodium chloride; the AOAC method uses magnesium sulfate and sodium acetate; and the EN method uses magnesium sulfate, sodium chloride, sodium citrate dihydrate, and citric acid monohydrate. In this study, we selected 2 g of anhydrous sodium sulfate, 1.0 g of C18, and 0.5 g of copper powder as purification agents and tested the recovery rates under two conditions: with and without the purification step.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we chose C18 as the adsorbent material. 45,46 According to the study by Jiao et al, we also found that adding copper powder to the extract solution during purication can improve the recovery rate of the extraction process 24,48 The purication salts used in each method are as follows: the original method uses magnesium sulfate and sodium chloride; the AOAC method uses magnesium sulfate and sodium acetate; and the EN method uses magnesium sulfate, sodium chloride, sodium citrate dihydrate, and citric acid monohydrate. In this study, we selected 2 g of anhydrous sodium sulfate, 1.0 g of C18, and 0.5 g of copper powder as purication agents and tested the recovery rates under two conditions: with and without the purication step.…”
Section: Analytical Methods Papermentioning
confidence: 99%
“…The detection and evaluation of copper compounds in the chelated or bound state are needed to advance the detection of residues of the pesticide in crops and to establish its maximum residue limits, which are important for human health. As the most widely used analytical tool, liquid chromatography tandem mass spectrometry (LC-MS/MS) has been reported for the analysis of pesticides in the environment and food matrix [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…They have the characteristics of a wide analysis range, sensitivity and resolution, low dosage and fast analysis speed. The QuEChERS method [ 33 , 34 , 35 , 36 ] has been used to monitor many pesticide residues in fruits and vegetables since its introduction, which is fast, simple, cheap and effective.…”
Section: Introductionmentioning
confidence: 99%